The effect of dietary magnesium and caseinphosphopeptides on bone metabolism in rats. Issue 12 (1st November 2017) - Liu, Guo; Miao, Jianyin; Sun, Shengwei; Luo, Zhen; Xia, Zumeng; Guo, Baoyan; Liu, Fei; Chen, Yunjiao; Ying, Danyang; Miao, Benchun; Cao, Yong
Abstract : The effect of magnesium supplementation with caseinphosphopeptides on bone metabolism in rats was investigated. Abstract : The effect of dietary magnesium (Mg) or caseinphosphopeptides (CPPs) on bone metabolism has been reported. However, few studies have investigated the effects of simultaneous supplementation of Mg and CPPs. Sixty-three 3-week-old Sprague-Dawley male rats were divided into seven groups and fed a specified diet for 45 days. Body characteristics, bone physicochemical indicators, and bone metabolism indicators relative to bone metabolism were analyzed. We found that, first, a dietary Mg deficiency resulted in increased bone formation and decreased bone resorption. Second, dietary Mg or CPP supplementation promoted bone formation and prevented bone resorption. Third, dietary Mg supplementation with CPPs also functioned to enhance bone formation and prevent bone resorption. There were synergistic effects on femur length, serum parathyroid hormone level and urinary deoxypyridinoline of the HS-Mg-CPP group (0.2% Mg, 0.1% CPPs). The increase in the femur length of the HS-Mg-CPP group compared with the control group was 6% which was much higher than that of HS-Mg (1%) or CPPs (5%). The induction in serum parathyroid hormone content in the HS-Mg-CPP group was 33% compared with the control group which was higher than that of the induction of the HS-Mg (19%) or CPP (23%) group. The induction in the deoxypyridinoline content of the HS-Mg-CPP (43%) group compared with the control group was remarkably higher than that of HS-Mg (8%) or CPPs (16%). Overall our results demonstrated that high doses of Mg (0.2%) and CPPs (0.1%) in combination produced synergistic effects on femur length, serum parathyroid hormone level and urinary deoxypyridinoline in rats, which is important for a better understanding of the effect of Mg and CPPs on bone metabolism.